Kenduri Wiwit as A Symbol Of Local Wisdom Relevant to Global Harmony - Fauziah, Giska Enny; Aprilia, Nurul Fitria; Aliyah, Nafilah Na’imatul (Proceedings of Annual Conference for Muslim Scholars, 2025)
The Kenduri Wiwit tradition is one of the Javanese forms of local wisdom that has been passed down through generations as an expression of gratitude for the harvest and harmonious life. In the current global context, cultural practices such as Kenduri Wiwit hold strategic value in fostering and strengthening universal human values. This study aims to analyze the symbolic meaning of Kenduri Wiwit as a form of local wisdom relevant to global harmony, as well as its role in nurturing love, gratitude, solidarity, and tolerance among communities. This research employs a qualitative descriptive approach using cultural ethnography methods, including participatory observation, in-depth interviews with community leaders, and literature studies on Javanese agrarian traditions. The findings indicate that Kenduri Wiwit functions not only as a religious and cultural ritual but also as a medium to strengthen social relationships, enhance solidarity across groups, and cultivate spiritual and ecological awareness. The values embedded in this tradition align with the principles of global harmony, including the cultivation of love, gratitude toward nature, tolerance, and togetherness in a plural society. In conclusion, Kenduri Wiwit can serve as a practical model of local wisdom that remains relevant for building and maintaining global harmony in contemporary society.